2021
DOI: 10.1016/j.amsu.2021.102683
|View full text |Cite
|
Sign up to set email alerts
|

The topical application of tranexamic acid to control bleeding in inguinal hernia surgery candidate patients: A randomized controlled trial

Abstract: Background and objectives Inguinal hernia surgery is a common procedure, especially for the elderly, who usually use anticoagulants and antiplatelet drugs. In this study, we evaluated the effectiveness of tranexamic acid (TXA) on the complications of inguinal hernia repair in patients using antiplatelets. Patients and methods This study is a randomized controlled trial that was performed during the 2018–2019 years. Forty patients with inguinal hernia and antiplatelet us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…One of the most common problems are the Abdominal wall hernias with predominant cause being the increased intra-abdominal pressure (7)(8)(9)(10). In 1962, tranexamic acid was discovered, essential medicines used to treat major traumatic injuries, excessive bleeding injuries, post-partum bleeding, surgeries, bleeding from nose, removal of tooth, and heavy menstrual bleeding (8)(9)(10)(11). Tranexamic acid is an easily available drug and its cost-effective with no dose adjustment required and safe in hepatic impairment (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most common problems are the Abdominal wall hernias with predominant cause being the increased intra-abdominal pressure (7)(8)(9)(10). In 1962, tranexamic acid was discovered, essential medicines used to treat major traumatic injuries, excessive bleeding injuries, post-partum bleeding, surgeries, bleeding from nose, removal of tooth, and heavy menstrual bleeding (8)(9)(10)(11). Tranexamic acid is an easily available drug and its cost-effective with no dose adjustment required and safe in hepatic impairment (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…Recently (in 2023) a cross-sectional study by Tarar et al has shown reduced risk of seroma formation in patients with ventral hernia, where in 81% of the patients seroma formation was improved within 5 days (9). Also, reduced number of complications have been reported with topical use of tranexamic acid in different surgeries (10). Khan et al has also reported reduction in seroma formation in 82.7% of patients with reduced drain output (11).…”
Section: Introductionmentioning
confidence: 98%
“…TXA has been widely administered among patients with bleeding disorders, trauma and among patients undergoing various types of surgery, for example, osteotomy, obstetrics, cardiovascular surgery, and hernia surgery [6,[15][16][17][18]. However, evidence suggested that TXA administration was found to be associated with increased risk of myocardial ischemia/infarction and other thrombotic complications (e.g.…”
Section: Introductionmentioning
confidence: 99%